Hands-on RESTful web services with ASP.NET Core 3 : design production-ready, testable, and flexible RESTful APIs for web applications and microservices - Resca, Samuele (Packt Publishing, 2019)
Get up to speed with the latest features of C# 8, ASP.NET Core 3 and .NET Core 3.1 LTS to create robust and maintainable web services Key Features Apply design patterns and techniques to achieve a reactive, scalable web service Document your web services using the OpenAPI standard and test them using Postman Explore mechanisms to implement a secure web service using client-side SSL and token authentication Book Description In recent times, web services have evolved to play a prominent role in web development. Applications are now designed to be compatible with any device and platform, and web services help us keep their logic and UI separate. Given its simplicity and effectiveness in creating web services, the RESTful approach has gained popularity, and this book will help you build RESTful web services using ASP.NET Core. This REST book begins by introducing you to the basics of the REST philosophy, where you'll study the different stages of designing and implementing enterprise-grade RESTful web services. You'll also gain a thorough understanding of ASP.NET Core's middleware approach and learn how to customize it. The book will later guide you through improving API resilience, securing your service, and applying different design patterns and techniques to achieve a scalable web service. In addition to this, you'll learn advanced techniques for caching, monitoring, and logging, along with implementing unit and integration testing strategies. In later chapters, you will deploy your REST web services on Azure and document APIs using Swagger and external tools such as Postman. By the end of this book, you will have learned how to design RESTful web services confidently using ASP.NET Core with a focus on code testability and maintainability. What you will learn Gain a comprehensive working knowledge of ASP.NET Core Integrate third-party tools and frameworks to build maintainable and efficient services Implement patterns using dependency injection to reduce boilerplate code and improve flexibility Use ASP.NET Core's out-of-the-box tools to test your applications Use Docker to run your ASP.NET Core web service in an isolated and self-contained environment Secure your information using HTTPS and token-based authentication Integrate multiple web services using resiliency patterns and messaging techniques Who this book is for This book is for anyone who wants to learn how to build RESTful web services with the ASP.NET Core framework to improve the sca ...